2014
DOI: 10.5901/mjss.2014.v5n23p1817
|View full text |Cite
|
Sign up to set email alerts
|

Are We Still Giving Our Money to Beggars? Prosocial Intention in between of Religion, Emotion, Corruption, and Government Policy Advocacy

Abstract: This research aimed to describe the dynamics of begging behavior in big cities in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
1
0
2
Order By: Relevance
“…This leads to one of the most important contributions of this research. If cost can be analogized with punishment and benefit can be analogized with reward, we can safely say that this conclusion is in line with Pérez and Kiss (as cited in Kurniadi, et al 2014) who state that "people are better in anticipating punishment compared to rewards" (p. 1823). Such perception of loss and anticipation of that loss may significantly contribute to strengthening an individual's motivation to change her/his habitual behaviors such as driving private cars.…”
Section: Resultssupporting
confidence: 73%
“…This leads to one of the most important contributions of this research. If cost can be analogized with punishment and benefit can be analogized with reward, we can safely say that this conclusion is in line with Pérez and Kiss (as cited in Kurniadi, et al 2014) who state that "people are better in anticipating punishment compared to rewards" (p. 1823). Such perception of loss and anticipation of that loss may significantly contribute to strengthening an individual's motivation to change her/his habitual behaviors such as driving private cars.…”
Section: Resultssupporting
confidence: 73%
“…Masalah pengemis merupakan fenomena yang ada di seluruh dunia, namun fenomena ini lebih banyak terjadi di negara-negara berkembang (Namwata, Mgabo& Dimoso, 2012), termasuk Indonesia. Jumlah pengemis di Indonesia sendiri mencapai 15 juta orang, dan jumlah ini termasuk dalam lima yang terbesar di dunia (Kurniady, Fresty, Kwan, Sharron & Abraham, 2014). Hampir seluruh kota-kota besar yang ada di Indonesia memiliki jumlah pengemis yang cukup tinggi (Purnama & Yuliani, 2015).Jumlahnya yang terus meningkat dalam masyarakat dikarenakan tidak adanya pekerjaan yang sesuai bagi orang-orang yang kurang atau tidak memiliki keterampilan pada suatu profesi khusus dan masyarakat tidak bisa secara efektif memecahkan permasalahan ini, sehingga mengemis merupakan sebuah sarana untuk mereka beradaptasi terhadap lingkungan agar dapat bertahan hidup (Ahamdi, 2010).…”
Section: Pendahuluanunclassified
“…1, Januari 2019 37 penghasilan (Namwata, Mgabo & Dimoso, 2012). Tingginya pendapatan yang diperoleh pengemis juga menjadi faktor mereka menjadikan mengemis sebagai profesi (Kurniady, Fresty, Kwan, Sharron & Abraham, 2014;Taufiki, 2015).Pengemis juga sudah tidak ada lagi rasa malu dalam menjalankan profesinya, sehingga mereka mau melakukan pekerjaan seperti itu tanpa menghiraukan harga diri (Riskawati & Syani, 2013). Padahal, Baron & Byrne (2004) menyatakan bahwa harga diri, merupakan aspek yang sangat penting dalam berfungsinya manusia, karena manusia memang sangat memperhatikan berbagai hal tentang diri, termasuk siapa dirinya, seberapa positif atau negatif seorang individu memandang dirinya, bagaimana citra yang ditampilkan pada orang lain, dan lain-lain.…”
Section: Pendahuluanunclassified
“…The research on begging behavior was also carried out in Indonesia. Kurniadi (2014) identified that the causative factors can be grouped into two, namely external factors (such as not having the capital to open a business, the difficulty of getting a job, the lure of high income from begging, offspring from parents who are beggars, environmental influences that the majority of whom become beggars) and internal factors (suffering from illness and laziness). Susanto and Yuhandra (2018) in their research found that beggars operate in groups and are organized.…”
Section: Y U S U F H a N A F I E T A Lmentioning
confidence: 99%